The Relationship of Home Renovation and Gender at Suburban Housing of Semarang City in Indonesia - Esariti, Landung; Putri, Marsella Dwi; Fauziah , Fitri; Dewi, Diah Intan Kusumo (Geographica Pannonica, 2021)
The purpose of this study was to explore gender influence on home renovation based on family life cycle in suburban housing of Bukit Kencana Jaya Semarang, Indonesia. Sixty households were interviewed and the resulting data were analyzed using the mix method. This attempt is important to determine the gender roles and relations influencing housing demand policies. The result showed most renovation activities were conducted on families with children, in addition to formulating two deductions. First, insingle and newcouples, gender productive roles tend to support house function in terms of economic existence and societal perception. Second, in families with children and elderly, these utilities serve as a habitat for income sources and welfare support.